Adsorption of Pb(II) Ions from Aqueous Solutions by Pyrolusite-Modified Activated Carbon Prepared from Sewage Sludge - Lu Fan; Yao Chen; Li Wang; Wenju Jiang (Adsorption Science & Technology)
In this study, activated carbons were prepared from sewage sludge by chemical activation, and modified with pyrolusite as a catalyst during activation and carbonization. The influence of the addition of the mineral on the properties of the produced activated carbons was evaluated. The modified activated carbons exhibited BET surface areas which were 11.31% higher than ordinary sludge-based activated carbons and had larger pore volumes. The results of adsorption experiments showed that the pyrolusite-added adsorbents performed better towards the removal of Pb(II) ions than those without pyrolusite addition. At an initial pH of 5.4 for the Pb(II) ion solution, addition of the pyrolusite-added activated carbon led to the effective removal of Pb(II) ions with an adsorption capacity of ca. 70 mg/g. The adsorption capacity towards Pb(II) ion removal also increased with increasing contact time and adsorbent dosage. Compared to adsorbents derived from various other materials, the pyrolusite-modified adsorbent had a relatively high Pb(II) ion adsorption capacity. Adsorption isotherm and kinetics studies showed that the adsorption of Pb(II) ions onto the pyrolusite-modified adsorbent was well fitted by the Langmuir isotherm and could be described by the pseudo-second-order kinetic model.